CLINICAL CARE THROUGH THE VIES OF BEHAVIOR ANALYSIS - Maria Fogassa Tonial Tavares, Franciele (Revista Gênero e Interdisciplinaridade, 2021)
This article aims to discuss clinical practice from the perspective of Behavior Analysis. This science is based on philosophical principles of radical behaviorism, dedicating itself to the study of the genesis of behavior. From now on, it is intended to contextualize the Behavior Analysis, its way of understanding man, mentioning some of its main concepts and resources used by the professional that bases his performance on this approach. It is also intended to contemplate some forms of existing therapies within this science and its forms of intervention.